Collaboration is key for new global tuberculosis strategy (The World Health Organization, 2014)
This month the World Health Assembly discusses the post-2015 global tuberculosis strategy and accompanying set of targets. Giovanni Battista Migliori tells Fiona Fleck how his institute - one of WHO's thousands of partners across the globe - can contribute in future to its implementation, once it is approved.